EFFECT OF INTERNAL CONTROL COMPONENTS AND REVENUE LEAKAGE: EVIDENCE FROM FINANCIAL INSTITUTIONS IN EDO STATE, NIGERIA - Efosa EHIMA; Otivbo Faith AMEDE (Gusau Journal of Accounting and Finance, 2025)
This study examines the relationship between internal control systems and revenue leakage in financial institutions in Edo State, specifically banks and microfinance institutions, by accessing how the various aspects of internal control, which includes control environment, risk assessment, control activities, information and communication, and monitoring, contribute to minimizing financial losses due to revenue leakage.This exploratory study utilised the administration of a well-structured 5-point Likert scale questionnaire to 384 employees of financial institutions in Edo State in gathering data. The instrument's reliability was confirmed with a Cronbach’s Alpha coefficient of 0.856. Data analysis involved the use of both descriptive statistics and multiple regression analysis to assess the relationship between internal control components and revenue leakage. The findings revealed that control activities had a significant relationship with revenue leakage, while other internal control components such as risk assessment, information and communication, and monitoring did not show a significant relationship with revenue leakage. This suggests that while control activities are crucial in minimizing revenue leakage, other components may require more effective implementation. Notably, the positive relationship of the coefficients contradicts the expected negative link between strong internal controls and revenue leakage. This may indicate that internal controls, though present, are not effectively enforced or are implemented superficially.  The study recommends strengthening of control activities and enhancing the integration of risk assessment and monitoring mechanisms to reduce revenue leakage in financial institutions.